Evaluasi Kesuburan Kimia Tanah di Lahan Kering Sub Daerah Aliran Sungai Samin Kabupaten Karanganyar - Retno Rosariastuti; Sri Hartati; Hery Widijanto; Endhah Wijoyo Utomo (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Tittle : The Evaluation of Soil Chemistry Fertility  In Dry Land Of Samin Sub Water Shead Area Kabupaten Karanganyar. The purpose of this research is in order to learn the parameter of the soil chemistry fertility based on the plants need which is planted in a dry field of Samin  Sub Water Sheet Area kabupaten Karanganyar and to learn the best of soil management alternative which is needed to keep the parameter of soil chemistry fertility in a good level. This research was done in September 2006 until April 2007. The design research of this research is qualitative descriptive phenomenology, by field survey and supported by quantitative laboratory analysis. The research variables are parameter of soil chemistry fertility (Organic C,  total N, C/N ratio, available P,  available K,  available Na, available Mg, available Ca, CEC, base saturation, pH H2O) and the soil management which is usually done by farmers (practice in cultivating the field,  fertilizing, kinds of plant which are planted, system of planting). The data analysis for parameter of soil chemistry fertility is matched with the need of plants grown and  soil management which usually done by farmers used triangulasi. The result of this research is  that the parameter of soil chemistry fertility which have fulfilled the plants need  are Ca and Mg. They have fulfilled the plants need in all LMU (Land Map Unit). The parameter of soil chemistry fertility which have exceed fulfilled the plants need  are fertilizing N and K. They are too much in all LMU.  The parameter of soil chemistry fertility which has not fulfilled the characteristic of plants are the high P deficiency caused by P adsorption in all LMU ; the level  of CEC is medium in all LMU except in LMU 1 and 3; the level of Organic C is medium in LMU 3, 4 and low in LMU 8, 9; the level of C/N ratio is high in LMU 1 and very high in LMU  5 (value >20); the level of soil pH is too acid for Mustard green, Green onion in LMU 6, 7, 8, 9 and too acid for Onion, Carrot in LMU SPL  8. Best alternative of  soil management needed are fertilizing N and K.They must be matched with the need of plants in all LMU; giving silikat (Si) for decreasing P adsorption in all LMU; giving organic fertilizer (cow manure, dose 20 ton/Ha), that must be maintained or increased in all LMU;  giving lime for increasing pH in LMU 6, 7, 8, 9.